Correlation between Hand-Eye Coordination and Wrist Flexibility on Short Service Ability in the PB Avanti Makassar Badminton Game - Suastika Nurafiati; Tri Angriawan; Achmad Karim; Herman Herman; Ariana Asri; Andi Sahrul Jahrir (Universitas Majalengka, 2023)
The ability to serve short in badminton is one of the most important strokes. The game of badminton begins with a short serve, so it is necessary to master the skills and basic techniques of the underhand serve. The research method used is quantitative research with correlational research. This correlational study involved two independent variables, namely hand-eye coordination and wrist flexibility, while the dependent variable was short serve ability in badminton. The population in this study was PB Avanti Makassar, with a sample of 30 athletes taken by random sampling. The data analysis technique used is the correlation coefficient. The results of the research conducted show that: 1). There is a significant relationship between hand-eye coordination and short serve ability in badminton with a value of r = 0.755. 2). There is a significant relationship between wrist flexibility and short serve ability in badminton, with a value of r = 0.731. 3). There is a significant relationship between hand-eye coordination and wrist flexibility, together with the short serve ability in badminton games, with a value of R = 0.853.